Developing an agenda for the decolonization of global health - McCoy, D.; Kapilashrami, A.; Kumar, R.; Rhule, E.; Khosla, R. (World Health Organization, 2023)
Colonialism, which involves the systemic domination of lands, markets, peoples, assets, cultures or political institutions to exploit, misappropriate and extract wealth and resources, affects health in many ways. In recent years, interest has grown in the decolonization of global health with a focus on correcting power imbalances between high-income and low-income countries and on challenging ideas and values of some wealthy countries that shape the practice of global health. We argue that decolonization of global health must also address the relationship between global health actors and contemporary forms of colonialism, in particular the current forms of corporate and financialized colonialism that operate through globalized systems of wealth extraction and profiteering. We present a three-part agenda for action that can be taken to decolonize global health. The first part relates to the power asymmetries that exist between global health actors from high-income and historically privileged countries and their counterparts in low-income and marginalized settings. The second part concerns the colonization of the structures and systems of global health governance itself. The third part addresses how colonialism occurs through the global health system. Addressing all forms of colonialism calls for a political and economic anticolonialism as well as social decolonization aimed at ensuring greater national, racial, cultural and knowledge diversity within the structures of global health.